ENTERPRISE ARCHITECTURE PLANNING FOR A DECISION SUPPORT SYSTEM TO IDENTIFY UNDERPRIVILEGED COMMUNITIES BASED ON TOGAF AND TOPSIS - Nining Ariati; Ahmad San Morino; Elsa Marindi; John Roni Coyanda (DiJITAC : Digital Journal of Information Technology and Communication, 2026)
The distribution of social assistance under the Program Keluarga Harapan (PKH) in Sukodadi Village, Sukarami District, Palembang, is still carried out conventionally, making it vulnerable to inaccuracies, subjectivity, and potential fraud in the recipient selection process. This problem concerns not only the accuracy of decision-making methods but also the weakness of information system governance at the architectural level. This study integrates the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method as a multi-criteria ranking engine with The Open Group Architecture Framework Architecture Development Method (TOGAF ADM) as the foundation for enterprise architecture planning. TOPSIS is used to rank 15 alternative PKH candidate recipients based on 10 criteria, while TOGAF ADM Phases A through F are applied to produce an enterprise architecture blueprint encompassing business, data, application, and technology architectures. The results indicate that the integration of both methods yields a Decision Support System (DSS) that is not only algorithmically accurate (Subroto as the best alternative with a preference value of 0.637) but also architecturally governed through a blueprint ready for replication across 107 sub-districts in Palembang City. Black box testing confirmed all system functions operate according to specifications, and user acceptance testing demonstrated high satisfaction levels.